2018
DOI: 10.3389/fpsyt.2018.00375
|View full text |Cite
|
Sign up to set email alerts
|

The Experience of Sleep Problems and Their Treatment in Young People at Ultra-High Risk of Psychosis: A Thematic Analysis

Abstract: We view sleep disruption as a contributory causal factor in the development of psychotic experiences. Clinical trials indicate that psychological interventions targeting insomnia result in improvements in both sleep and psychotic experiences. The aim of this study was to gain the perspective of young people at ultra-high risk of psychosis on their sleep problems and associated psychological treatment. Interviews were conducted with 11 patients, aged 15–22 years, at ultra-high risk of psychosis who had received… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 26 publications
1
13
0
1
Order By: Relevance
“…Experiences of insomnia were characterised by a surge of negative thoughts and feelings at bedtime, caused by a lack of distraction. This is consistent with previous findings suggesting that bedtime rumination causes difficulties falling asleep (Conroy, et al, 2017;Waite, et al, 2018), although a lack of distraction has not previously been highlighted as the potential mechanism.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Experiences of insomnia were characterised by a surge of negative thoughts and feelings at bedtime, caused by a lack of distraction. This is consistent with previous findings suggesting that bedtime rumination causes difficulties falling asleep (Conroy, et al, 2017;Waite, et al, 2018), although a lack of distraction has not previously been highlighted as the potential mechanism.…”
Section: Discussionsupporting
confidence: 92%
“…A few studies have examined features of treatment that might improve sleep problems in adolescents with mental health difficulties (Conroy et al, 2017;Waite et al, 2018). For example, Waite et al (2018) found that adolescents improved their sleep by learning more about sleep hygiene.…”
mentioning
confidence: 99%
“…However, further support for the early presence and persistence of sleep disturbances comes from studies in bipolar disorder suggesting sleep disturbances are evident before illness onset ) and persistent over a 5-year study period (Kanady et al, 2015) and from studies in early psychosis in schizophrenia . Also, research investigating the role of sleep disturbance in individuals with an ultra-high risk for development of psychosis is emerging, pointing to the importance of addressing and treating sleep disturbances early on (Lunsford-Avery et al, 2017; F. Waite et al, 2018;Zanini et al, 2015). Still there is an urgent need for more research on sleep disturbances in the early phases of severe mental disorders, and to firmly establish their potential as an early intervention target (Bradley et al, 2018;.…”
Section: The Frequency Of Sleep Disturbances In Severe Mental Disordersmentioning
confidence: 99%
“…In qualitative interviews, participants described achieving meaningful change in both sleep and well-being by developing a 'repertoire of skills'. 29 The treatment now requires testing in a randomised trial to determine the effects on psychotic experiences and the potential to prevent the onset of psychosis.…”
mentioning
confidence: 99%